Which Female Cancer Patients Fail to Receive Fertility Counseling Before Treatment in the State of Georgia - Chin, Helen B. (Fertil Steril, 2016)
OBJECTIVE: To assess which characteristics are associated with failure to receive fertility counseling among a cohort of young women diagnosed with cancer. DESIGN: A population-based cohort study. SETTING: Not applicable. PATIENTS: A total of 1,282 cancer survivors, of whom 1,116 met the inclusion criteria for the analysis. INTERVENTIONS: None. MAIN OUTCOME MEASURE(S): The main outcome in this study was whether or not women reported receiving any information on how cancer treatment might affect their ability to become pregnant at the time of their cancer diagnosis. RESULTS: Forty percent of cancer survivors reported that they did not receive fertility counseling at the time of cancer diagnosis. Women were more likely to fail to receive counseling if they had a high school education or less (OR=1.90, 95% CI: 0.97, 3.70) or if they had a prior birth (OR=1.92, 95% CI: 1.31, 2.81). Cancer related variables that were associated with a lack of counseling included not receiving chemotherapy as part of treatment (OR=4.39, 95% CI: 2.96, 6.51) and diagnosis with certain cancer types. CONCLUSIONS: Counseling about the risk of infertility and available fertility preservation options is important to cancer patients. Additionally, counseling can make women aware other adverse reproductive outcomes such as early menopause and its associated symptoms. Less educated women and parous women are at particular risk of not getting fertility-related information. Programs that focus on training not just the oncologist, but also other healthcare providers involved with cancer care, to provide fertility counseling may help expand access.